Expression of scaffolding, signalling and contractile‐filament proteins in human myometria: effects of pregnancy and labour - Riley, M.; Baker, P. N.; Tribe, R. M.; Taggart, M. J. (Journal of cellular and molecular medicine, 2005)
Successful parturition requires the co‐ordination of numerous myometrial signalling events to allow for timely and efficient uterine contractions. Late pregnancy and labour onset in humans may be associated with changes in the expression of myometrial proteins implicated in such uterine contractile signal integration. Accordingly, in myometria from non‐pregnant women and pregnant women, not in labour or in labour, we examined the content of putative plasmalemmal scaffolding proteins (caveolin‐1 and ‐2) and compared these to the proportions of signal transducing rho‐associated kinases (ROK α and β) and contractile filament‐associated proteins α‐actin, myosin regulatory light chain (MLC20) and h‐caldesmon. There was no effect of pregnancy or labour on the proportion of caveolin, ROK β or α‐actin. However, pregnancy was associated with a decrease in ROK α and MLC20 such that ROK α: α‐actin and MLC20: α‐actin ratios were reduced compared to myometria of non‐pregnant women. In contrast, h‐caldesmon was up‐regulated in pregnancy resulting in an elevated h‐caldesmon: α ‐actin ratio. There were, however, no further significant changes in ROK α, MLC20 or h‐caldesmon expression with spontaneous or oxytocin‐induced labour. These data suggest that the mechanism(s) integrating myometrial signalling events with the onset of human labour does not involve differential alterations of the cellular expressions of caveolins, ROK, α ‐actin, MLC20 or h‐caldesmon.